Night on earth - Jarmusch, Jim, 1953-; Jarmusch, Jim, 1953-; Jarmusch, Jim, 1953-; Ryder, Winona, 1971-; Benigni, Roberto; Dalle, Béatrice, 1964- (Jim Jarmusch collection, 1991)
Πέντε παράξενες, διασκεδαστικές και τρυφερές ιστορίες από πέντε διαφορετικά σημεία του κόσμου.